NILAI-NILAI PENDIDIKAN AKHLAK DALAM KISAH AISYAH R.A PADA BUKU SULAIMAN AN-NADAWI DAN RELEVANSINYA TERHADAP PENDIDIKAN AKHLAK ISTRI DI ERA MODERN - Agus Faisal Asyha; Waluyo Erry Wahyudi; Fenny Febrianti Pesawal (Insititut Agama Islam Agus Salim Metro Lampung, 2024)
Abstract This research is motivated by the presence of moral deviations in Indonesian society, including theft, sexual misconduct, allegations, self-indulgence, and adultery. These issues highlight a decline in societal morals, which is concerning, especially among women who play a crucial role in Islamic upbringing. Women are seen as the backbone of Islamic values, as they are future mothers who will teach their children about Islam. The book